Combination of Geriatric Nutritional Risk Index and Carcinoembryonic Antigen to Predict the Survival of Patients With Colorectal Cancer - Xie, Hailun; Wei, Lishuang; Yuan, Guanghui; Liu, Mingxiang; Liang, Yanren; Gao, Shunhui; Wang, Qiwen; Lin, Xin; Tang, Shuangyi; Gan, Jialiang (Frontiers in Nutrition, 2022)
Background: This study explored the value of the combination of Geriatric Nutritional Risk Index (GNRI) and carcinoembryonic antigen (CEA) for the prognosis assessment of CRC patients. Methods: This study retrospectively enrolled 1014 CRC patients who underwent surgery between 2012 and 2014. Kaplan-Meier and log-rank tests were used to compare survival differences. Cox proportional hazards regression analysis was used to assess risk factors associated with progression-free survival (PFS) and overall survival (OS). Nomograms were constructed to predict the prognosis of CRC patients. Randomized internal validation was used to confirm the predictive accuracy of the prognostic nomograms. Results: The GNRI-CEA score was established by combining GNRI and CEA. Compared with patients with normal GNRI-CEA scores, patients with mild/moderate/severe GNRI-CEA scores had significantly lower survival (PFS, 68.99% vs. 57.75% vs. 41.34% vs. 31.36%, p<0.001; OS, 68.99% vs. 57.75% vs. 41.34% vs. 31.36%, p<0.001). The GNRI-CEA score is an independent factor predicting the prognosis of CRC patients. The risk of death was 2-fold higher in patients with low GNRI and high CEA than in those with both normal GNRI and CEA [PFS, hazard ratio (HR), 2.339; 95% confidence interval (CI), 1.656–3.303; p <0.001; OS, HR, 2.340; 95% CI, 1.645–3.329; p <0.001). Prognostic nomograms had good resolution and accuracy in predicting 1–5 year PFS and OS. Randomized internal validation showed that the nomograms were reliable. Conclusion: The combination of GNRI and CEA can effectively stratify the prognosis of CRC patients. The nomogram established based on the two indices can provide a personalized reference for prognostic assessment and clinical decision-making for CRC patients.